Optimization modeling for strengthening the quality of educational institution services : POP-SDM method - Elisha Yochanan; Soewarto Hardhienata; Eka Suhardi (Educenter : Jurnal Ilmiah Pendidikan, 2023)
The quality of service in higher education institutions is very important because it can affect student satisfaction, learning outcomes, and the reputation of the institution. Therefore, higher education institutions must continuously strive to improve the quality of the services they provide. This research aims to build an empirical model of service quality for educational institutions by looking for variables that influence strengthening service quality based on data and information from sources. This research uses qualitative methods through an interview and observation process with study program staff at the Indonesian Defense University Education Institute in Bogor, West Java, Indonesia. In this research, it was found that the dominant variables that influence the quality of teaching staff services are (1) organizational climate, (2) training effectiveness, (3) job satisfaction, (4) professionalism, (5) empowerment of educators, (6) motivational work, and (7) professional commitment. Therefore, improving the quality of educational institutions is important and must be a main concern for institutions.